HOW BRAND REPUTATION, FEATURES, AND EASE SHAPE INTENTION TO USE myBCA - Firda Khairani; Fiska Kusumawati (Jurnal Manajemen dan Bisnis Performa, 2025)
In Indonesia, digital banking usage continues to accelerate, with myBCA recording 6.9 billion successful transactions in 2024, up 128 % year-on-year. This competition intensifies pressure to tailor digital offerings to Gen Z preferences. This study aims to determine the influence of brand reputation, service features, and ease of use on Generation Z’s intention to use the myBCA application in DKI Jakarta. A quantitative descriptive method with purposive sampling was employed; online questionnaires were answered by 100 respondents and processed using SPSS version 23 for statistical analysis. Results show that brand reputation, service features, and ease of use each have a positive and significant effect on intention to use, partially and collectively. Collectively, these factors explain 67.7 % of the variance in intention to use. These insights imply that BCA should strengthen its digital brand image, streamline and integrate key features to match Gen Z needs, and optimize the user interface to sustain engagement, guide further interface refinements, and secure competitive advantage in digital banking.